The Reflection of Highest Value of Islam in the Protection of Debtors in Execution of Separatist Creditors - Teddy Asmara (Jurnal Akta, 2022)
The execution by separatist creditors without going through court proceedings as regulated in Article 55 and Article 56 of Act No. 37 of 2004 is contrary to the justice of Pancasila. The method used was a non-doctrinal method. Based on the data obtained, it can be seen that the execution of bankruptcy as regulated in Article 55 and Article 56 of Act No. 37 of 2004 prioritizes the interests of separatist creditors, this is further complicated by the existence of a legal culture which shows that the execution of bankruptcy with collateral rights without having to go through bailing in court, the meaning of debtor insolvency should be an examination in court or through bailing related to the debtor's ability to pay off his debts, not solely based on the analysis and views of separatist creditors alone. This is clearly implicitly based on Article 28D of the 1945 Constitution of the Republic of Indonesia and automatically contradicts the values of Pancasila social justice. This means that in the legal policy of bankruptcy execution, it must be able to create a balance of protection of rights between creditors and debtors, in accordance with the view of respect for human values or human rights awards in the form of equality before the law so as to be able to realize social justice execution of bankruptcy that is able to protect the interests of separatist creditors while protecting debtors.